Electrical Characterisation of Aδ-Fibres Based on Human in vivo Electrostimulation Threshold - Tanaka, Shota; Gomez-Tames, Jose; Wasaka, Toshiaki; Inui, Koji; Ueno, Shoogo; Hirata, Akimasa (Frontiers in Neuroscience, 2021)
Electrical stimulation of small fibres is gaining attention in the diagnosis of peripheral neuropathies, such as diabetes mellitus, and pain research. However, it is still challenging to characterise the electrical characteristics of axons in small fibres (Aδ and C fibres). In particular, in vitro measurement for human Aδ-fibre is difficult due to the presence of myelin and ethical reason. In this study, we investigate the in vivo electrical characteristics of the human Aδ-fibre to derive strength–duration (S–D) curves from the measurement. The Aδ-fibres are stimulated using coaxial planar electrodes with intraepidermal needle tip. For human volunteer experiments, the S–D curve of Aδ-fibre is obtained in terms of injected electrical current. With the computational analysis, the standard deviation of the S–D curve is mostly attributed to the thickness of the stratum corneum and depth of the needle tip, in addition to the fibre thickness. Then, we derive electrical parameters of the axon in the Aδ-fibre based on a conventional fibre model. The parameters derived here would be important in exploring the optimal stimulation condition of Aδ-fibres.